Trigeminal neuroplasticity underlies allodynia in a preclinical model of mild closed head traumatic brain injury (cTBI). (August 2016) - Mustafa, Golam; Hou, Jiamei; Tsuda, Shigeharu; Nelson, Rachel; Sinharoy, Ankita; Wilkie, Zachary; Pandey, Rahul; Caudle, Robert M.; Neubert, John K.; Thompson, Floyd J.; Bose, Prodip
Abstract: Post-traumatic headache (PTH) following TBI is a common and often persisting pain disability. PTH is often associated with a multimodal central pain sensitization on the skin surface described as allodynia. However, the particular neurobiology underlying cTBI-induced pain disorders are not known. These studies were performed to assess trigeminal sensory sensitization and to determine if sensitization measured behaviorally correlated with detectable changes in portions of the trigeminal sensory system (TSS), particularly trigeminal nucleus, thalamus, and sensory cortex. Thermal stimulation is particularly well suited to evaluate sensitization and was used in these studies. Recent advances in the use of reward/conflict paradigms permit use of operant measures of behavior, versus reflex-driven response behaviors, for thermal sensitization studies. Thus, to quantitate facial thermal sensitization (allodynia) in the setting of acute TBI, the current study utilized an operant orofacial pain reward/conflict testing paradigm to assess facial thermal sensitivity in uninjured control animals compared with those two weeks after cTBI in a rodent model. Significant reductions in facial contact/lick behaviors were observed in the TBI animals using either cool or warm challenge temperatures compared with behaviors in the normal animals. These facial thermal sensitizations correlated with detectable changes in multiple levels of the TSS. The immunohistochemical (IHC) studies revealed significant alterations in the expression of the serotonin (5-HT), neurokinin 1 receptor (NK1R), norepinephrine (NE), and gamma-aminobutyric acid (GABA) in the caudal trigeminal nucleus, thalamic VPL/VPM nucleus, and sensory cortex of the orofacial pain pathways. There was a strong correlation between increased expression of certain IHC markers and increased behavioral markers for facial sensitization. The authors conclude that TBI-induced changes observed in the TSS are consistent with the expression of generalized facial allodynia following cTBI. To our knowledge, this is the first report of orofacial sensitization correlated with changes in selected neuromodulators/neurotransmitters in the TSS following experimental mild TBI. Highlights: cTBI induced significant orofacial allodynia. This orofacial allodynia was accompanied by significant alterations in the expression of the 5-HT, NK1R, NE, and GABA throughout the trigeminal sensory pathway. These neuromodulators in primary, secondary, and tertiary levels of the trigeminal sensory pathway may contribute generalized facial allodynia and/or headache-like pain behavior following TBI. These observations suggest potentially multiple targets for intervention to addresses changes as an effective strategy to control orofacial pain after TBI. Facial allodynia is one of the major outcomes in headache or trigeminal injury related pain following TBI patients.